The Boolean algebra is used to describe certain logic design made up with several logic gates and wires connecting them.
$A+B=B+A$, and $AB=BA$.
$(A+B)+C=A+(B+C)$, and $(AB)C=A(BC)$.
$A(B+C)=AB+AC$.
$A+AB=A$, and $A(A+B)=A$.
This theorem shows that $B$ will be ‘absorbed’ in this form of expression.
$AB+A\bar{B}=A$, and $(A+B)(A+\bar{B})=A$.
$A+\bar{A}B=A+B$.
$A+\bar{A}B=A+AB+\bar{A}B=A+(A+\bar{A})B=A+B$.
${A+BC=(A+B)(A+C)}$
Why: $(A+B)(A+C)=A+AC+BA+BC$, and $A+AC+BA=A$.
$AB+\bar{A}C+BC=AB+\bar{A}C$, and $AB+\bar{A}C+BCD=AB+\bar{A}C$.
Use $BC$ to absorb $BCD$.
$\overline{A\bar{B}+\bar{A}B}=\bar{A}\bar{B}+AB$.
XNOR = XOR + NOT.
$$ \begin{align*}\overline{X_1X_2\cdots X_n}=\bar{X}_1+\bar{X}_2+\cdots+\bar{X}_n\\\overline{X_1+X_2+\cdots+X_n}=\bar{X}_1\bar{X}_2\cdots\bar{X}_n\end{align*} $$
By changing operators in an expression in this way you get its dual expression:
For a equation it’s dual expression is still valid. For example: